The Role of Thoracic Ultrasonography and Airway Endoscopy in the Diagnosis of Equine Asthma and Exercise-Induced Pulmonary Hemorrhage - Chiara Maria Lo Feudo (MDPI AG, 2021)
Mild-moderate (MEA), severe (SEA) equine asthma and exercise-induced pulmonary hemorrhage (EIPH) are common respiratory disorders in horses. The present retrospective study aims to evaluate the role of ultrasonography and endoscopy in the diagnosis of these conditions. Three hundred and three horses were included and divided into SEA, MEA and MEA + EIPH groups, on the basis of history, clinical examination and bronchoalveolar lavage fluid (BALf) cytology; scores were assigned to lung ultrasonography, pharyngeal lymphoid hyperplasia (PLH), tracheal mucus (TM) and tracheal bifurcation edema (TB). These scores were compared between groups, and their associations with age, BALf cytology, tracheal wash microbiology and between endoscopic and ultrasonographic scores were statistically analyzed. Ultrasonographic scores were higher in the SEA and MEA + EIPH groups and associated with increased BALf neutrophils and hemosiderophages. The PLH score was higher in younger horses affected by MEA and EIPH and associated with increased eosinophils and hemosiderophages. TM and TB scores were greater in older horses affected by SEA, associated with increased neutrophils and inversely correlated with hemosiderophages. Moreover, TM grade was negatively correlated with mast cells. Thoracic ultrasonography and airway endoscopy can provide useful information about the inflammatory status of upper and lower airways in the horse.